Collectin-11 regulates osteoclastogenesis and bone maintenance via a complement-dependent mechanism - Mark C. Howard; Conrad A. Farrar; Christopher L. Nauser; Yusun Jeon; Anastasia Polycarpou; Dorota Smolarek; Roseanna Greenlaw; Martyn Foster; Peter Garred; Daniela A. Vizitiu; Subhankar Mukhopadhyay; Steven H. Sacks (Proceedings of the National Academy of Sciences, 2026)
The human developmental disorder 3MC syndrome (Malpuech, Michels, Mingarelli, and Carnevale) features skeletal deformities associated with a deficiency of the pattern recognition molecule collectin-11 (CL-11), yet the underlying molecular and cellular mechanisms remain uncertain. Here, we demonstrate that CL-11 deletion alone does not produce skeletal abnormalities in mice; however, combined deficiencies of CL-11 with complement components MASP-2 (lectin pathway), complement factors B, or C3 (alternative pathway amplification) result in marked vertebral bone loss and spinal curvature by 12 wk of age. Ex vivo osteoclast (OCL) differentiation from bone marrow–derived cells of these double-knockout mice was profoundly impaired but was substantially restored by CL-11 supplementation. This dependence on CL-11 and complement was recapitulated in human OCLs derived from induced pluripotent stem cell lines. CL-11 and the membrane attack complex (C5b-9) colocalized to OCLs and their precursors in normal bone from embryonic development through to adulthood. Together, these findings identify CL-11 as a key regulator of osteoclastogenesis and bone homeostasis acting in concert with complement-mediated signaling, and they nominate CL-11 as a potential therapeutic target in conditions involving dysregulated osteoclast function and bone remodeling.